Taḥlīlu al Kalimãti al Ughniyyati li Nancy Ajram (Dirãsatun Taqãbiliyyatun baina al Lughati al ‘Arabiyyati al Fuṣḥã wa al ‘Ãmiyyati) - Saputra, Ridho Herman; Buska, Wahyudi (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2023)
This research aims to reveal the implementation of the use or use of Amiyah and Fuscha languages in Nancy Nabil Ajram's singing which is contained in several of her albums. There are two kins bof Arabic, namely Fusha Arabic and Amiyah Arabic. Along with the development of the age, there are literary works in the form of songs in the Amiyah language. The Egyptian Amiyah language is the language that is used or functionhed as the language of daily communication among Egyptians, while Fusha Arabic is an Arabic language which is familiar or popular throughout the world on or know as the language of the Qur’an. This study uses qualitative research methods, namely research whoise results are presented or described descriptively. The initial stage in thbis research os to collect related data and the include it in a scientific work/thesis. The result of the research above are changes in letters, sentences and structures, for example, from the world يااللي to the world من, a change from the world بحبك to أحبكwh the letter أ changes to the letters ب. The world وحدي أنا changes to وأنا بنفسي, the world لياأنا becomes وانا بالنسبة there are significant changes to the lyrics of the song, for example على وعدي، يا وعدي، لوحدي أنا becomes أعدك، أعدك أنت فقط من أجلي, there are 141 different in the terms of structure, namely: 26 fi’il, 26 fa’il, 26 mubtada, and 26 khabar.